The IARI: harbinger for chrysanthemum growers’ prosperity - Singh, Shalandra (Indian Horticulture, 2019)
Mr P. Pradeep Chand, B. Venkata Swami Reddy and P. Sri Ramulu started cultivation of chrysanthemum in open fields with two local varieties. They came across an article on new chrysanthemum varieties developed by the IARI, New Delhi, in vernacular magazine, the Annadatta and the Indian Horticulture, in January 2010. Having read about the range of varieties available in the Division of Floriculture and Landscaping, they decided to visit IARI, New Delhi, to see the varieties and collect yellow and white coloured varieties as per their local market demands. They also keep themselves updated with the latest developments in floriculture by regularly reading the Indian Horticulture published by the (DKMA) ICAR, New Delhi. The reading of the Indian Horticulture has played a vital role in revolutionizing the life-style of flower growers, claim all the three progressive farmers.